2013
DOI: 10.1597/12-094
|View full text |Cite
|
Sign up to set email alerts
|

Early Mother-Child Interaction and Later Quality of Attachment in Infants With an Orofacial Cleft Compared to Infants Without Cleft

Abstract: Objective :  The main objective of this study was to assess mother-child patterns of interaction in relation to later quality of attachment in a group of children with an orofacial cleft compared with children without cleft. Design :  Families were contacted when the child was 2 months old for a direct assessment of mother-child interaction and then at 12 months for a direct assessment of the child's attachment. Data concerning socioeconomical information and posttraumatic stress symptoms in mothers were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Regardless of its reason, our finding that, in the context of cleft lip, parents gaze less to the infant's mouth may be of clinical significance. Previous studies have found infants born with a cleft lip to show no temperamental difference, but are less communicative (Montirosso et al, 2012), and cooperative (Habersaat et al, 2013) during early interactions, while their mothers show decreased responsiveness and sensitivity to infant social behaviour (Field & Vega-Lahr, 1984;Murray et al, 2008;Speltz, Goodell, Endriga, & Clarren, 1994), negatively affecting later infant cognitive outcomes (Murray et al, 2008;Speltz et al, 2000;Wasserman & Allen, 1985). All these studies have, however, focused on infants of at least 2 months of age, with no available data on earlier behaviours of mothers and infants with cleft lip.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of its reason, our finding that, in the context of cleft lip, parents gaze less to the infant's mouth may be of clinical significance. Previous studies have found infants born with a cleft lip to show no temperamental difference, but are less communicative (Montirosso et al, 2012), and cooperative (Habersaat et al, 2013) during early interactions, while their mothers show decreased responsiveness and sensitivity to infant social behaviour (Field & Vega-Lahr, 1984;Murray et al, 2008;Speltz, Goodell, Endriga, & Clarren, 1994), negatively affecting later infant cognitive outcomes (Murray et al, 2008;Speltz et al, 2000;Wasserman & Allen, 1985). All these studies have, however, focused on infants of at least 2 months of age, with no available data on earlier behaviours of mothers and infants with cleft lip.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, difficulties in interactional skills have been observed [4]. Habersaat et al [5] describes that babies with CLP interact less with their mother at 2 months of age, compared to controls. Other studies [6] point the fact that mothers are less responsive and less sensitive in the interpretation of their infant's signals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Habersaat et al. () showed that children with a cleft were more difficult and less cooperative during interactions with their mothers, as compared to children without a cleft; however, no significant differences were found in mothers in that study.…”
mentioning
confidence: 60%